The interaction of xenobiotics and anaesthetic agents with hepatic microsomal stearate desaturase - Manca, Veronica (Division of Medical Biochemistry and Structural Biology, 2018)
This thesis comprises an investigation into the reaction of halogenated xenobiotics and anaesthetic agents, with hepatic microsomal stearate desaturase. The levels of stearate desaturase in the hepatic microsomes were routinely elevated by re-feeding the experimental animals a high carbohydrate diet. The interaction of the xenobiotics with stearate desaturase was assessed by monitoring their effects on the redox steady state of hepatic microsomal cytochrome b₅, in the presence and absence of cyanide.